Fundamentals of electric circuits - Alexander, Charles K. (McGraw-Hill Higher Education, 2004)
This book discusses all topics in linear circuit analysis. The emphasis is on problem-solving (odd-numbered answers are included). The contain consists of DC circuits, AC circuits, and advanced circuit analysis. The computer circuit analysis program is used throughout, and a brief tutorial on is appended. The included CD-ROM contains which allows students to create circuits, analyze prebuilt circuits, and work through virtual lab assigmments.